An epidemiological surveillance system for COVID-19 in a dental teaching center between 2021 and 2023 - Ramirez-Revollar, Marie (2025)
Objective: To describe the follow-up of epidemiological surveillance of COVID-19 positive cases in a dental teaching center in Peru between 2021 and 2023. Materials and methods: A cross-sectional study was conducted as part of a COVID-19 surveillance plan in a dental teaching center of a Peruvian university. The study was conducted between June 2021 and April 2023, reaching a total of 1,623 records, in which students and faculty members participated. Results: A total of 120 COVID-19 positive cases were reported during the surveillance period, with the highest peak observed during the third wave. The results showed that the year with the highest number of cases was 2022, accounting for 92.5% (n = 111), and the most affected group was that of postgraduate students, representing 57.5% (n = 69). Conclusions: This study highlights the importance of implementing effective epidemiological surveillance systems in clinical-educational settings, particularly during public health emergencies such as the COVID-19 pandemic. The collected data revealed that most positive cases were concentrated during the third wave, particularly among postgraduate students, highlighting the urgent need to strengthen preventive measures in these high-risk groups. The absence of reported cases in the first four months of 2023 suggests successful containment, mainly attributed to the implementation of strict biosafety protocols and the progress of vaccination. Epidemiological surveillance systems must remain up to date to ensure a safe environment for all those involved.